Horn trace element profiles of managed rhinoceros species and comparisons to matched livers and wild African rhinoceros horns - Terri L. Roth; Sarah L. Rebolloso; Elizabeth M. Donelan; Louisa A. Rispoli; Elizabeth W. Freeman; John P. Buchweitz (PLoS ONE, 2026)
Rhino horn is composed of keratin which contains numerous minerals and metals that may provide insight into the species’ environment and health. Our goals were to identify horn trace elements that differ according to sex, species, and continent, and those that reflect liver loads. Samples from 82 horns representing (male.female): 25.16 black rhino, 13.16 white rhino, 6.3 greater one-horned (GOH) rhino, 0.1 Sumatran rhino, and 2.0 undetermined were analyzed for 14 trace elements: arsenic, barium, cadmium, chromium, cobalt, copper, iron, lead, manganese, mercury, molybdenum, selenium, thallium, and zinc. A subset of matched liver tissues (n = 21) also was analyzed for up to 12 of the elements. Horn trace element concentrations did not differ by sex ( p ≥ 0.05), but several were impacted by species and continent. Copper concentrations in white rhino horn trended higher compared to those measured in black rhino horn ( p = 0.051), whereas selenium and molybdenum concentrations were higher in black rhino horn compared to those in white rhino horn ( p < 0.05), and cobalt was higher in black rhino horn compared to GOH rhino horn ( p < 0.05). Horns from Africa (n = 7) were higher in arsenic and barium and lower in copper and zinc ( p < 0.05) compared to those from the United States (n = 52). Both arsenic and selenium were positively correlated with matched liver tissue values; arsenic across all species (Spearman’s p = 0.017, rho = 0.659) and selenium within black rhinos ( p = 0.004, rho = 0.790). Rhino horn trace element concentrations differed by species, and preliminarily between continents, reflecting population trends in element status, but most were not significantly correlated to individual liver loads.